Role of synaptophysin, chromogranin and CD56 in adenocarcinoma and squamous cell carcinoma of the lung lacking morphological features of neuroendocrine differentiation: a retrospective large-scale study on 1170 tissue samples - Kriegsmann, Katharina; Zgorzelski, Christiane; Muley, Thomas; Christopoulos, Petros; Thomas, Michael; Winter, Hauke; Eichhorn, Martin E.; Eichhorn, Florian; Winterfeld, Moritz von; Herpel, Esther; Goeppert, Benjamin; Stenzinger, Albrecht; et al. (BMC cancer, 2021)
Synaptophysin, chromogranin and CD56 are recommended markers to identify pulmonary tumors with neuroendocrine differentiation. Whether the expression of these markers in pulmonary adenocarcinoma and pulmonary squamous cell carcinoma is a prognostic factor has been a matter of debate. Therefore, we investigated retrospectively a large cohort to expand the data on the role of synaptophysin, chromogranin and CD56 in non-small cell lung cancer lacking morphological features of neuroendocrine differentiation.